Paradigma Bimbingan Konseling dalam Kurikulum Merdeka - Huda, Miftahul; Hidayah, Rifa (Universitas Muria Kudus, 2024)
Facing changes in technology and Merdeka Belajar curriculum policies, counselors need to be innovative in counseling services. The challenges of the guidance and counseling profession in the era of industrial revolution 4.0 require adaptation and innovation. This research uses qualitative methods with literature studies, utilizing various sources such as books, journals and institutional reports. The role of guidance and counseling teachers is important to align learning with the Merdeka Belajar program, encouraging the development of High Order Thinking Skills (HOTS). The implementation of the Guidance and Counseling service policy in the Minimum Competency Assessment allows for a holistic assessment and develops programs and provides appropriate intervention services. The main goal of Guidance and Counseling teachers is to help students recognize themselves, function as service providers so that each individual can develop optimally, achieve personal needs, and become a complete and independent individual. Menghadapi perubahan teknologi dan kebijakan kurikulum Merdeka Belajar, konselor perlu inovatif dalam layanan konseling. Tantangan profesi bimbingan dan konseling pada era revolusi industri 4.0 membutuhkan adaptasi dan inovasi. Penelitian ini menggunakan metode kualitatif dengan studi pustaka, memanfaatkan berbagai sumber seperti buku, jurnal, dan laporan lembaga. Peran guru bimbingan dan konseling penting untuk menyelaraskan pembelajaran dengan program Merdeka Belajar, mendorong pengembangan High Order Thinking Skills (HOTS). Penerapan kebijakan layanan Bimbingan dan Konseling dalam Asesmen Kompetensi Minimum memungkinkan penilaian holistik dan menyusun program serta memberikan layanan intervensi yang sesuai. Tujuan utama guru Bimbingan dan Konseling adalah membantu peserta didik mengenali diri mereka, berfungsi sebagai penyedia layanan agar setiap individu dapat berkembang optimal, mencapai kebutuhan pribadi, dan menjadi individu utuh serta mandiri.